In support of western regional resource and transmission planning coordination - Unidentified author; Center for the New Energy Economy, publisher (Colorado State University. Libraries, 2021)
Produced in partnership by Gridworks and CNEE, this report stems from the facilitated conversations of the WIRED Transmission Planning and Development Working Group, in which leading Western transmission operators and policymakers collaborate to develop a shared vision for coordinated regional resource and transmission planning. This report concludes that existing "bottom up" transmission planning processes will not lead to the inter-regional, cost-effective transmission we need in the West. Rather, we recommend a coordinated regional resource and transmission planning process. The report outlines steps for beginning this process.--taken from website.
Keywords: Energy policy; Renewable energy sources -- Law and legislation -- United States; resource planning; transmission planning; development